1998
DOI: 10.1177/004051759806800310
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Biaxial Tensile Deformation Behavior of Spunbonded Nonwovens

Abstract: An analysis is presented to predict the biaxial tensile behavior of spun-bonded non woven fabrics using knowledge of the stress-strain behavior of their constituent fibers and their orientation angle distribution. Nonlinearity in fiber stress-strain behavior is considered in order to predict fabric stresses in the longitudinal and transverse direc tions under biaxial loading conditions. Only a special case of biaxial loading is con sidered in which the transverse strain is forced to be zero, i.e., strip biaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…The finite element model is able to successfully predict Poisson's ratios as high as 1.3 in a uniaxial test. Although still lower than the experimental values obtained in a uniaxial test, these values are much higher than the experimental values obtained by biaxial testing [ 5 ] . The main reason for such high values of Poisson's s ratio in uniaxial testing lies in the easy buckling of fibers under compression as well as the directional dependence of fabric stiffness.…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…The finite element model is able to successfully predict Poisson's ratios as high as 1.3 in a uniaxial test. Although still lower than the experimental values obtained in a uniaxial test, these values are much higher than the experimental values obtained by biaxial testing [ 5 ] . The main reason for such high values of Poisson's s ratio in uniaxial testing lies in the easy buckling of fibers under compression as well as the directional dependence of fabric stiffness.…”
Section: Resultscontrasting
confidence: 74%
“…The orientation distribution function and fiber stressstrain behavior were used as input parameters. A detailed procedure for obtaining these parameters has been reported in previous publications [ 4,5 ] . For the 9.0 dpf PET fiber used in fabrics A and C, the bilinear fit constants were K, ,T 225.3974, K, = 17.3745, Kz = 5.6290, and c,.…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that the results generated from the analytical theory accurately matched the data from experimental studies. Later, their previous work was extended in 18 by utilizing the same unit cell (see Figure 1) under biaxial tensile loading. It was shown that, stress predictions for the longitudinal direction were consistent with the experimental results.…”
Section: Tensile Behaviormentioning
confidence: 99%
“…BASIC EQUATIONS ' j ' BASIC' EQUATIONS j Letting [K] be the stiffness matrix of the structure, {D} the nodal degree(s) of freedom (dof) of the structure, and ( R ) the total load on the structure nodes, the toaddisplacement equation of a static geometric nonlinear problem can be stated as 1 In this section, we outline the change of variables in the triple integral and the derivation of the strain-displacement matrix [B]. The details can be found in earlier work [ 16].…”
Section: Finite Element Displacement Formulationmentioning
confidence: 99%